Impact of serum albumin concentration and neutrophil-lymphocyte ratio score on gastric cancer prognosis - Teresa Virgínia Ribeiro Parente da Costa (2020)
INTRODUCTION/AIM - Serum albumin concentration (COA) and neutrophil-lymphocyte ratio (NLR) could reflect immunological and nutritional status. We aim to evaluate the impact of COA-NLR score on the prognosis of gastric cancer (GC). MATERIAL AND METHODS - We perform a retrospective analysis on a database of 637 GC cases, between January 2010 and December 2017. 396 patients met the inclusion criteria for this study. COA-NLR score was defined as: COA under 35 g/L and NLR value of 2.585 or higher - score 2; one of these conditions - score 1; and neither - score 0. RESULTS - In our population (n=203), 87 patients were classified as score 0, 82 as score 1 and 34 as score 2. COA-NLR score was significantly associated with DFS (HR 1,674; CI95% 1,115 - 2,513; p=0,013) and with OS (HR 2,072; CI95% 1,531 - 2,805; p<0,001). Kaplan-Meier curves analysis and log-rank test revealed that a higher score of COA-NLR predicted a worse OS (p<0,001) and DFS (p=0,03). COA-NLR was an independent prognostic factor for OS when adjusted to pStage and age (adjusted HR 1,566; CI95% 1,145 - 2,143; p=0,005). CONCLUSIONS - Preoperative COA-NLR score was significantly associated with worse OS and DFS and, in this way, with worse prognosis on GC patients submitted to curative-intent resectional surgery.